GPT-4 and Beyond : Advancements in AI Language Models - Venkata Subrahmanya Vijaykumar Jandhyala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the groundbreaking advancements and implications of GPT-4, the latest iteration in the Generative Pre-trained Transformer series. It delves into GPT-4’s enhanced comprehension and contextual awareness, multilingual proficiency, expanded knowledge base, multimodal capabilities, and improved safety and ethical considerations. The article provides quantifiable improvements and practical implications across various domains, including natural language processing, machine translation, research assistance, education, and content creation. It also addresses the challenges and limitations of the model, such as biases and computational requirements, while discussing future directions in AI development. The piece concludes with projections for future AI capabilities, emphasizing more human-like reasoning, handling of complex tasks, and seamless integration with other systems, while also highlighting the ethical considerations and challenges that accompany these advancements.